Menkes disease complicated by concurrent ACY1 deficiency: A case report - Mauri, Alessia; Saielli, Laura Assunta; Alfei, Enrico; Iascone, Maria; Marchetti, Daniela; Cattaneo, Elisa; Di Lauro, Anna; Antonelli, Laura; Alberti, Luisella; Bonaventura, Eleonora; Veggiotti, Pierangelo; Spaccini, Luigina; et al. (Frontiers in Genetics, 2023)
Introduction: Menkes disease is an X‐linked recessive condition caused by mutations in the ATP7A gene, which leads to severe copper deficiency. Aminoacylase-1 deficiency is a rare inborn error of metabolism caused by homozygous or compound heterozygous variant in the ACY1 gene, characterized by increased urinary excretion of specific N-acetyl amino acids. Case presentation: We report an infant with neurological findings such as seizures, neurodevelopmental delay and hypotonia. Metabolic screening showed low serum copper and ceruloplasmin, and increased urinary excretion of several N-acetylated amino acids. Whole-exome sequencing analysis (WES) revealed the novel de novo variant c.3642_3649dup (p.Ala1217Aspfs*2) in the ATP7A gene, leading to a diagnosis of Menkes disease, and the simultaneous presence of the homozygous ACY1 variant c.1057C>T (p.Arg353Cys) causative of Aminoacylase-1 deficiency. Conclusions: Our patient had two rare conditions with different treatment courses but overlapping clinical features. The identified novel ATP7A mutation associated with Menkes disease expands the ATP7A gene spectrum.